Wybrane aspekty zakazu prowadzenia pojazdów orzekanego jako środek probacyjny - Łucarz, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the driving ban adjudicated on the basics of Art. 67 § 3 of the Penal Code. This measure is distinguished by the fact that it is always optional, and can be adjudicated only for two years. It concerns the cases of perpetrators who are involved in traffic and committed specific traffic offenses. Failure to comply with the ban can bring, in accordance with Art. 68 § 2 of the Penal Code, a conditionally discharged procedure. The matter of controversy is the nature of the legal ban on driving with a conditional discharge. In the author’s opinion the ban on driving with a conditional discharge is a probation measure associated with submission to probation.
Keywords: zakaz prowadzenia pojazdów; środek probacyjny; orzecznictwo